The make or buy debate: Considering the limitations of domestic production in Tanzania - Wilson Kinsley; Kohler Jillian; Ovtcharenko Natalia (BMC, 2012)
Abstract Background In order to ensure their population's regular access to essential medicines, many least developed countries and developing countries are faced with the policy question of whether to import or manufacture drugs locally, in particular for life-saving antiretroviral medicines for HIV/AIDS patients. In order for domestic manufacturing to be viable and cost-effective, the local industry must be able to compete with international suppliers of medicines by producing sufficiently low cost ARVs. Methods This paper considers the 'make-or-buy' dilemma by using Tanzania as a case study. Key informant interviews, event-driven observation, and purposive sampling of documents were used to evaluate the case study. The case study focused on Tanzania's imitation technology transfer agreement to locally manufacture a first-line ARV (3TC + d4T + NVP), reverse engineering the ARV. Results Tanzania is limited by weak political support for the use of TRIPS flexibilities, limited production capacity for ARVs and limited competitiveness in both domestic and regional markets. The Ministry of Health and Social Welfare encourages the use of flexibilities while others push for increased IP protection. Insufficient production capacity and lack of access to donor-financed tenders make it difficult to obtain economies of scale and provide competitive prices. Conclusions Within the "make-or-buy" context, it was determined that there are significant limitations in domestic manufacturing for developing countries. The case study highlights the difficulty of governments to make use of economies of scale and produce low-cost medicines, attract technology transfer, and utilize the flexibilities of the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). The results demonstrate the importance of evaluating barriers to the use of TRIPS flexibilities and long-term planning across sectors in future technology transfer and manufacturing initiatives.